(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Whole the world in societies adult those who did not and to labor incompetent persons such as social to the defense needs individuals financial support of provision legal basics social of justice basis is considered Many of countries Crime Codes Articles 122 and 123 are valid within the framework, including in Uzbekistan those who did not and old to parents relatively material help obligations from doing neck extortion heavy to crimes directed. This articles such to help depends of those who welfare and value protection to do for very important​